2013
DOI: 10.3389/fcimb.2013.00055
|View full text |Cite
|
Sign up to set email alerts
|

Role and regulation of heme iron acquisition in gram-negative pathogens

Abstract: Bacteria that reside in animal tissues and/or cells must acquire iron from their host. However, almost all of the host iron is sequestered in iron-containing compounds and proteins, the majority of which is found within heme molecules. Thus, likely iron sources for bacterial pathogens (and non-pathogenic symbionts) are free heme and heme-containing proteins. Furthermore, the cellular location of the bacterial within the host (intra or extracellular) influences the amount and nature of the iron containing compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
109
0
14

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(126 citation statements)
references
References 135 publications
3
109
0
14
Order By: Relevance
“…2A). Some strains in these species have been shown to utilize extracellular hemin as a sole source of iron (15). Kvitko et al (25) experimentally identified the Burkholderia pseudomallei hmuRSTUV cluster that encodes a TonB-dependent ABC transporter system for the uptake and utilization of hemin, and in the present study we found a similar gene cluster on chromosome 2 in ATCC 17616 ( Fig.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…2A). Some strains in these species have been shown to utilize extracellular hemin as a sole source of iron (15). Kvitko et al (25) experimentally identified the Burkholderia pseudomallei hmuRSTUV cluster that encodes a TonB-dependent ABC transporter system for the uptake and utilization of hemin, and in the present study we found a similar gene cluster on chromosome 2 in ATCC 17616 ( Fig.…”
Section: Resultssupporting
confidence: 82%
“…Constitutive and highlevel production of HemP in DF1 would be expected to lead to overproduction of HmuS. Some HmuS homologues from other genera have been reported to function as heme oxygenases that degrade heme to release free iron (15,17). If the ATCC 17616 HmuS protein has such an activity, then the overproduced HmuS protein in DF1 would result in drastic increases in the levels of free iron produced from intracellular heme, and the increased levels of free iron would in turn generate large amounts of ROS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is a pivotal component of the innate immune response through its role in the generation of toxic oxygen and nitrogen intermediates [12] . Pathogens are involving growth, proliferation and disease processes, can not directly use Fe 2+ from the host body, but compete with the host for Fe 2+ by iron uptake-related proteins to fulfill their iron needs [13] . TonB protein, a periplasmic protein, plays an important role in energy-dependent transport of iron siderophores of Gram-negative bacteria as well as a virulence factor [14] .…”
Section: Iron (Fe 2+mentioning
confidence: 99%
“…Receptors at the bacterial surface recognize the free heme or hemoproteins and transport heme to the periplasm. Once inside the cell, iron is released from heme (8). More elaborate heme acquisition systems secrete heme-scavenging molecules, the hemophores, which extract heme from host hemoproteins and deliver it to an outer membrane receptor for internalization (8).…”
Section: Introductionmentioning
confidence: 99%